The Impact of Parental Financial Socialisation on Financial Decision-Making of Young Black African Adults in Rural and Low-Income Area in South Africa - Ndou, Adam (International Journal of Economics and Financial Issues, 2023)
This study investigated the impact of parental financial socialisation on financial decision-making of young black African adults in rural and low-income area in South Africa. Data was collected through self-administered questionnaire from 423 young black African adults in Fetakgomo Tubatse and Intsika Yethu local municipalities, low-income and rural areas in South Africa. Multiple regression analysis was used to test the relationship between parental financial behaviour, parental financial monitoring, parental financial discussion, parental financial communication, and parental financial teaching with financial decision-making. The results indicated that parental financial communication had a significant positive relationship with financial decision-making. While parental financial behaviour, parental financial monitoring, parental financial discussion, and parental financial teaching had no positive relationship with financial decision-making. Therefore, the overall results indicated that parental financial socialisation has no impact on financial decision-making of young black African adults in rural and low-income area in South Africa. This study provided recommendations to parents, young black African adults, financial educators, financial services institutions, and financial counsellors.